2015
DOI: 10.7717/peerj-cs.18
|View full text |Cite
|
Sign up to set email alerts
|

How do you feel, developer? An explanatory theory of the impact of affects on programming performance

Abstract: Affects-emotions and moods-have an impact on cognitive activities and the working performance of individuals. Development tasks are undertaken through cognitive processes, yet software engineering research lacks theory on affects and their impact on software development activities. In this paper, we report on an interpretive study aimed at broadening our understanding of the psychology of programming in terms of the experience of affects while programming, and the impact of affects on programming performance. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 84 publications
7
43
0
Order By: Relevance
“…When grouping codes for low cognitive performance and process-related productivity, approximately 55% of the related in-text references deal with productivity and performance drops. Those results are in line with and support the related work in software engineering research (Graziotin et al, 2015a(Graziotin et al, , 2014bMüller and Fritz, 2015;Khan et al, 2010;Wrobel, 2013) which quantified the relationship or attempted to explain the link.…”
Section: Addressing the Research Questionssupporting
confidence: 88%
See 3 more Smart Citations
“…When grouping codes for low cognitive performance and process-related productivity, approximately 55% of the related in-text references deal with productivity and performance drops. Those results are in line with and support the related work in software engineering research (Graziotin et al, 2015a(Graziotin et al, , 2014bMüller and Fritz, 2015;Khan et al, 2010;Wrobel, 2013) which quantified the relationship or attempted to explain the link.…”
Section: Addressing the Research Questionssupporting
confidence: 88%
“…We also add that addressing happiness can impact the very core prerequisites for software development: cognitive performance, motivation, and a positive atmosphere at the workplace. We note that previous research (Graziotin et al, 2015a) has suggested that intervening on the affect of developers might have relatively low costs and astonishing benefits.…”
Section: Recommendations For Practitionersmentioning
confidence: 67%
See 2 more Smart Citations
“…Much of this can be avoided by task rotation, by taking better decisions, and by actually listening to developers. Several top causes are related to the perception of inadequacy of the self and others, which encourages recent research activities on intervening on the affect of developers [3].…”
Section: What Makes Developers Unhappy?mentioning
confidence: 83%